Polycyclic aromatic hydrocarbons in water samples from a Nigerian bitumen seepage: Gas chromatography- mass spectrometry quantification (Bangladesh Journal of Scientific and Industrial Research, 2018)
Bitumen exploration was flagged off at Irele, a Nigerian field in 2003. The relationship between the seepage pollutants and receiving water bodies is the focus of this study. We hereby present the polycyclic aromatic hydrocarbons (PAHs) level in two categories of bitumen contaminated waters; source (RS) and delivery (RD) points. Results were compared with uncontaminated water (RC) as control experiment. The PAHs were extracted by Liquid-Liquid extraction using dichloromethane and analyzed by Gas chromatography with mass spectrometer detector (GC-MS). The mean concentration of PAHs was 8.39, 3.93 and 0.57 ppb for source, delivery point and control respectively. The Benzo[e]pyrene concentrations obtained were higher than 1-10 ppb in most samples, indicating anthropogenic and petrogenic sources of the pollutants. Most of the PAH concentrations obtained were within natural concentrations, However, Benzo (e) pyrene and Indenol (1, 2, 3 – cd) pyrene exceeded the expected limit. The predominance of 4-6 member ring showed that the PAHs were more of pyrolytic than mixed sources. Method validation gave the Limit of Detection (LOD) and Limit of Quantification values in the range of 0.03-0.12 and 0.10-0.61 respectively. The Pearson product moment correlation (PPMC) coefficient (r) was used to determine the interactions of the PAHs detected with parametric factors. All the physicochemical parameters studied except pH shows positive correlation. Statistical test at P